China growth accounting and growth sustainability. - Low, Yi Shi. (2013)
China used to be the world’s largest economy in the fourteenth century. Due to economic mismanagement, the country has gone through a trough and now re-emerges as a fast developing country with outstanding growth rates. Its remarkable performance in economic reforms have sparked studies to be done with respect to China’s growth accounting. Most papers concentrate on China’s growth pre and post-reform but limited studies have been done on the impacts of China’s accession into World Trade Organization (WTO) using growth accounting. Modifying the standard Cobb-Douglas production function to account for human capital, this paper focuses on the analysis of China’s growth pre- and post-WTO accession using data from 1985-2011. Data collected were mainly from China’s National Bureau of Statistics (NBS), China Ministry of Education and World Bank. Our main findings have shown that WTO has been beneficial to China’s economic development. China’s growth accelerated from 9.06 percent pre-WTO (1985-2001) to 10.04 percent post-WTO (2002-2011). Growth averaged at 9.44 percent from 1985-2011 and more than 55 percent of growth is driven by physical capital accumulation. However, we have also observed an increasing contribution of total factor productivity (TFP) growth to GDP growth especially after China’s accession into WTO. While the success of economic reforms deserves to be complimented, the paper also looks forward and explores the sustainability of China’s growth in the future. Issues such as diminishing returns to capital investments, impending ageing demographics and rising political pressures to fulfill World Trade Organization (WTO) obligations must be addressed. Looking forward, China should aim to increase human capital and improve TFP in order to achieve sustainable growth. Results of increasing TFP and human capital growth rates from our empirical analysis provide an encouraging outlook.